Aspirin for the prevention of preeclampsia: A systematic review and meta-analysis of randomized controlled studies - Wang, Yixiao; Guo, Xiaojun; Obore, Nathan; Ding, Hongjuan; Wu, Chengqian; Yu, Hong (Frontiers in Cardiovascular Medicine, 2022)
Background: The results of randomized controlled studies on aspirin for the prevention of preeclampsia (PE) are conflicting, and some of the related meta-analyses also have limitations or flaws. Data sources: Pubmed, Embase, and Cochrane Central Register of Controlled Trials databases, with no time or language restrictions. Study Eligibility Criteria: Randomized controlled studies comparing aspirin for the prevention of PE. Methods: Systematic reviews were performed according to the Cochrane Manual guidelines. A fixed-effects model or a random-effects model was chosen to calculate pooled relative risks with 95% confidence intervals based on the heterogeneity of the included studies. The study aimed to investigate the effect of aspirin on the development of PE in high-risk and general women. Publication bias was assessed by funnel plots. All included studies were assessed for bias by the Cochrane Manual of Bias Assessment. Subgroup analyses were conducted on the duration of aspirin intervention, aspirin dose, and the region in which the study was conducted, to explore the effective duration and dose of aspirin and to try to find sources of heterogeneity and publication bias. Results: A total of 39 articles were included in the study, of which 29 studied high-risk women of PE (20133 patients in total) and 10 studied the general women (18911 patients in total). Aspirin reduced the incidence of PE by 28% (RR 0.72, 95% CI 0.62-0.83) in women at high risk for PE. Aspirin was associated with a 30% reduction in the incidence of PE in the general women (RR 0.70, 95% CI 0.52-0.95), but a sensitivity analysis found that the results of studies using aspirin in the general women were unreliable. The results of subgroup analysis showed that aspirin ≤81mg/day (RR 0.69, 95% CI 0.57-0.83) had a better protective effect than doses >81mg/day (RR 0.80, 95% CI 0.68-0.96); Aspirin was more effective and reliable in reducing the incidence of PE at 12-16 weeks' gestation (RR 0.62, 95% CI 0.53-0.74) than at 12-28 weeks' gestation (RR 0.74, 95% CI 0.56-0.97); included Heterogeneity and publication bias of studies may arise mainly from studies conducted in the Asian region.